Porous moisture absorption material, porous moisture absorption piece, dehumidification device, preparation method of porous moisture absorption material and preparation method of hydrogel
By using a single-layer mesh-shaped porous adsorption mesh and hydrogel-hygroscopic salt composite in hygroscopic materials, the problem of insufficient adsorption rate and balanced adsorption amount of existing hygroscopic materials is solved, and more efficient air dehumidification and water collection effects are achieved.
Patent Information
- Application Number
- CN202510123739.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-26
AI Technical Summary
The adsorption rate and equilibrium adsorption amount of existing hygroscopic materials at different humidity levels are insufficient, resulting in low air dehumidification and water collection efficiency.
Porous absorbent material is used, which includes a single-layer mesh porous adsorption mesh and a hydrogel-absorbent salt composite covering the grid line, ensuring that the mesh remains penetrated at all times.
The adsorption rate and equilibrium adsorption amount are significantly improved, and the efficiency of porous hygroscopic materials in the air dehumidification and water collection process is enhanced.
Smart Images

Figure CN119633779A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of air dehumidification or air water collection, and specifically to a porous hygroscopic material, a porous hygroscopic component, a dehumidification device, a method for preparing the porous hygroscopic material, and a method for preparing a hydrogel. Background Art
[0002] Adsorption air dehumidification is to capture water in the air through the physical or chemical action of hygroscopic materials to achieve the dehumidification effect. Adsorption air water collection uses energy to desorb hygroscopic materials on the basis of adsorption air dehumidification to release and collect water. Hygroscopic materials play an important role in the entire dehumidification and water collection process. In the water adsorption process, the water adsorption capacity mainly involves the adsorption rate and equilibrium adsorption amount at different humidity levels. In the water collection process, the average daily water collection amount is mainly considered, and the average daily water collection amount is related to the equilibrium adsorption amount and the number of daily adsorption-desorption cycles. The number of daily adsorption-desorption cycles is closely related to the adsorption rate. Therefore, whether in the field of air dehumidification or air water collection, the goal is to increase the adsorption rate of hygroscopic materials, followed by the equilibrium adsorption amount of hygroscopic materials.
[0003] The first prior art related to the present application is the Chinese patent application publication CN119019610A, which discloses a hygroscopic transparent hydrogel and its preparation method and application. The hygroscopic transparent hydrogel is polymerized by zwitterionic monomers and hydrophilic monomers in a hygroscopic salt solution. The zwitterionic monomers make the hygroscopic transparent hydrogel contain cations and anions, thereby effectively preventing the leakage and migration of hygroscopic salts. The hygroscopic transparent hydrogel is autonomously adhered to the upper surface of the solar cell panel as a hygroscopic material, thereby cooling the solar cell panel. The hygroscopic material has an adsorption capacity of 0.5g / g after 9h in an environment with a relative humidity of 90%, and an equilibrium adsorption capacity of 0.56g / g.
[0004] The second prior art related to the present application is the Chinese patent application publication text CN116180446A, which discloses a method for preparing a PNIPAAm hydrogel-based pile fabric with super moisture absorption and water release. First, the pile fabric is prepared, and then the pile fabric is placed in a solution containing monomers to undergo a polymerization reaction, so that a layer of PNIPAAm hydrogel with a porous structure is coated on the surface of the pile fabric. Finally, polydopamine nanoparticles and polypyrrole are coated on the surface of the pile fabric, and it is immersed in a lithium chloride solution by alternating hot and cold treatment to obtain a hygroscopic material. The hygroscopic material has a three-dimensional structure, so that the maximum level of light absorption can be achieved through multiple reflections and scattering. The gaps between fibers treated with PNIPAAm hydrogel are directly filled with a large amount of hydrogel with a highly interconnected pore structure. Its purpose is to quickly evaporate and collect the moisture collected at night under light conditions. The hygroscopic curve of the above-mentioned hygroscopic material is shown in the attached specification.Figure 5 As shown, in an environment with a relative humidity of 30%, the equilibrium adsorption amount was not reached after 12 hours, and the equilibrium adsorption amount was no higher than 0.7g / g. The adsorption time was not announced, but it was estimated to be no less than 4 hours. Summary of the invention
[0005] The purpose of the present application is to overcome the above-mentioned defects or problems existing in the background technology, and to provide a porous hygroscopic material, a porous hygroscopic element, a dehumidification device, a method for preparing a porous hygroscopic material and a method for preparing a hydrogel, wherein the porous hygroscopic material has a higher adsorption rate than the above-mentioned two prior arts.
[0006] In order to achieve the above purpose, the following technical solutions are adopted:
[0007] The first technical solution involves a porous hygroscopic material, which includes: a porous adsorption net, which is in a single-layer mesh and whose material is hydrophilic; and a hydrogel-hygroscopic salt composite material, which covers at least part of the grid lines of the porous adsorption net and keeps at least part of the mesh holes always connected, the hydrogel-hygroscopic salt composite material includes a hydrogel and a hygroscopic salt that are integrated with each other, and the hydrogel is an ionic hydrogel.
[0008] The second technical solution is based on the first technical solution, wherein, in the portion of the hydrogel-hygroscopic salt coated grid line, the number of mesh holes that always remain through accounts for greater than or equal to 60%.
[0009] The third technical solution is based on the first technical solution, wherein the mesh size of the porous adsorption net is between 100 mesh and 300 mesh.
[0010] The fourth technical solution is based on the third technical solution, wherein the mesh size of the porous adsorption net is preferably 200 meshes.
[0011] The fifth technical solution is based on the first technical solution, wherein the material of the porous adsorption net is preferably nylon or polyurethane or glass or silicon carbide.
[0012] The sixth technical solution is based on the first technical solution, wherein the mass percentage of the hygroscopic salt in the hydrogel-hygroscopic salt composite material is between 20% and 70%.
[0013] The seventh technical solution is based on the sixth technical solution, wherein the mass percentage of the hygroscopic salt in the hydrogel-hygroscopic salt composite material is between 35% and 70%.
[0014] The eighth technical solution is based on the first technical solution, wherein the hygroscopic salt is one or more of lithium chloride, calcium chloride, magnesium chloride and lithium bromide.
[0015] The ninth technical solution is based on the eighth technical solution, wherein the hygroscopic salt is preferably lithium chloride.
[0016] The tenth technical solution is based on any one of the first to ninth technical solutions, wherein the hydrogel contains cations.
[0017] The eleventh technical solution is based on the tenth technical solution, wherein the cation is preferably a quaternary ammonium cation.
[0018] The twelfth technical solution is based on any one of the first to ninth technical solutions, wherein the hydrogel contains anions.
[0019] The thirteenth technical solution is based on the twelfth technical solution, wherein the anion is preferably one or more of carboxyl, carboxylate, sulfonate and phosphate.
[0020] The fourteenth technical solution is based on any one of the first to ninth technical solutions, wherein the hydrogel contains cations and anions.
[0021] The fifteenth technical solution is based on the fourteenth technical solution, wherein the cation is preferably a quaternary ammonium cation, and the anion is preferably one or more of a carboxyl group, a carboxylate group, a sulfonate group and a phosphate group.
[0022] The sixteenth technical solution is based on the fifteenth technical solution, wherein the anion is more preferably a carboxyl group and / or a carboxylate group.
[0023] The seventeenth technical solution relates to a porous hygroscopic component, which comprises a support and the porous hygroscopic material as described in any one of the first to sixteenth technical solutions, wherein the support supports the porous hygroscopic material.
[0024] The eighteenth technical solution is based on the seventeenth technical solution, wherein the porous hygroscopic material is planar, the number of the porous hygroscopic materials is at least two, and each porous hygroscopic material is arranged at intervals along a direction perpendicular to its plane.
[0025] The nineteenth technical solution relates to a dehumidification device, which includes a heater, a condenser and a porous hygroscopic component as described in the seventeenth or eighteenth technical solution; the heater desorbs the porous hygroscopic material on the porous hygroscopic component by heating, and the condenser is used to form condensed water from the water vapor formed after the desorption of the porous hygroscopic material.
[0026] The twentieth technical solution is based on the nineteenth technical solution, and further includes a water collector, which is connected to the condenser to collect condensed water generated by the condenser.
[0027] The twenty-first technical solution is based on the nineteenth technical solution, and further includes a fan, wherein the fan is used to make the air heated by the heater form convection to desorb the porous hygroscopic material on the porous hygroscopic component.
[0028] The twenty-second technical solution is based on the twenty-first technical solution, wherein the porous hygroscopic materials are arranged in a vertical direction, and the heated air passes through each of the porous hygroscopic materials.
[0029] The twenty-third technical solution is based on the nineteenth technical solution, and further includes a control unit, which controls the heater to start when the amount of adsorbed water of the porous hygroscopic material reaches or exceeds a first threshold, and controls the heater to shut down when the amount of adsorbed water reaches or is lower than a second threshold; the first threshold is higher than the second threshold.
[0030] The twenty-fourth technical solution is based on the twenty-third technical solution, wherein the control unit includes a gravimeter and a controller, the gravimeter is used to detect the weight of the porous hygroscopic component, and the controller characterizes the amount of water adsorbed by the porous hygroscopic material according to the weight of the porous hygroscopic component.
[0031] The twenty-fifth technical solution is based on the twenty-third technical solution, wherein the control unit includes a hygrometer and a controller, the hygrometer is used to detect the ambient humidity, and the controller characterizes the amount of water adsorbed by the porous hygroscopic material based on the ambient humidity detected by the hygrometer according to the period after the heater is turned off and the period after it is turned on.
[0032] The twenty-sixth technical solution relates to a method for preparing a porous hygroscopic material, which is used to prepare the porous hygroscopic material as described in any one of the first to sixteenth technical solutions, and comprises the following steps:
[0033] Step 1: placing the hydrogel in an aqueous solution of hygroscopic salt;
[0034] Step 2: After the hydrogel swells, mechanical crushing is performed to form a micron-sized hydrogel-hygroscopic salt coating; and
[0035] Step 3: Apply the hydrogel-hygroscopic salt coating to a hydrophilic and monolayer porous adsorption network and dry it.
[0036] The twenty-seventh technical solution is based on the twenty-sixth technical solution, wherein, in step 1, the mass ratio of the hydrogel to the aqueous solution of the hygroscopic salt is between 1 to 40 and 1 to 20; in the aqueous solution of the hygroscopic salt, the molar ratio of the hygroscopic salt is between 0.5 mol / L and 3 mol / L.
[0037] The twenty-eighth technical solution is based on the twenty-seventh technical solution, wherein, in step 1, the mass ratio of the hydrogel to the aqueous solution of the hygroscopic salt is preferably between 1 to 25 and 1 to 35; in the aqueous solution of the hygroscopic salt, the molar ratio of the hygroscopic salt is preferably between 1 mol / L and 2 mol / L.
[0038] The twenty-ninth technical solution is based on the twenty-sixth technical solution, wherein, in step 2, the mechanical crushing is carried out by stirring.
[0039] The thirtieth technical solution is based on the twenty-sixth technical solution, wherein, in step 3, the method of coating the hydrogel-hygroscopic salt coating onto the porous adsorption network includes dipping, spraying, brushing, rod coating, and spin coating.
[0040] The thirty-first technical solution is based on the thirtieth technical solution, wherein in step 3, the method of coating the hydrogel-hygroscopic salt coating onto the porous adsorption network is preferably dip coating.
[0041] The thirty-second technical solution relates to a method for preparing a hydrogel, which is used to prepare a hydrogel, and the hydrogel is used to prepare a porous hygroscopic material as described in the sixteenth technical solution, wherein the hydrogel is obtained by a free radical polymerization reaction of a first monomer containing a quaternary ammonium salt cationic group and a second monomer containing a carboxyl group and / or a carboxylate anion group, a cross-linking agent and an initiator under conditions of a first solvent, followed by purification and drying; the free radical polymerization reaction is a front-end polymerization reaction; the cross-linking agent and the initiator are both hydrophilic; the first monomer and the second monomer are monomers containing carbon-carbon double bonds; and the first solvent is water or a hydrophilic alcohol.
[0042] The thirty-third technical solution relates to the thirty-second technical solution, wherein the cross-linking agent is preferably an acrylamide cross-linking agent; the initiator is preferably a peroxide or azo initiator; the first monomer is preferably acryloyloxyethyltrimethylammonium chloride and / or (3-acrylamidepropyl)trimethylammonium chloride; and the second monomer is preferably acrylic acid and / or sodium acrylate.
[0043] The thirty-fourth technical solution is based on the thirty-second technical solution, wherein the molar ratio of the second monomer to the first monomer is less than or equal to 5 to 3.
[0044] The thirty-fifth technical solution is based on the thirty-fourth technical solution, wherein the molar ratio of the second monomer to the first monomer is preferably 1 to 3.
[0045] The thirty-sixth technical solution is based on the thirty-second technical solution, wherein the free radical polymerization reaction also includes a third monomer, and the third monomer is a monomer without an ionic group and containing a carbon-carbon double bond; the third monomer is preferably an acrylate, methacrylate, acrylamide or methacrylamide monomer.
[0046] Compared with the prior art, the above solution has the following beneficial effects:
[0047] In the first technical solution, the hydrogel is an ionic hydrogel, which can form a valence bond with the hygroscopic salt, thereby having a stronger salt-carrying capacity, making the hygroscopic salt less likely to leak or result, and being dispersed in the hydrogel skeleton.
[0048] In the first technical solution, the porous adsorption network material is hydrophilic and can better combine with the hydrogel-hygroscopic salt composite material, thereby more effectively avoiding the agglomeration of the hydrogel-hygroscopic salt composite material.
[0049] The most important technical contribution of this application is that, through creative assumptions, experiments and comparative analysis, it is determined that the use of a single-layer porous adsorption net to carry a hydrogel-hygroscopic salt composite material has the highest adsorption rate compared to the prior art. Among them, the hydrogel-hygroscopic salt composite material covers at least part of the grid lines of the porous adsorption net and keeps at least part of the mesh holes connected all the time, which is the most important technical feature of this application that distinguishes it from the prior art.
[0050] The "coating" here refers to the hydrogel-hygroscopic salt composite material three-dimensionally coating the grid lines of the single-layer porous adsorption network, which not only enables the hydrogel-hygroscopic salt composite material to obtain the maximum specific surface area, but also enables the hydrophilic porous adsorption network and the hydrogel-hygroscopic salt composite material to have the maximum contact area, thereby more effectively avoiding the agglomeration of the hydrogel-hygroscopic salt composite material. It should be noted that under this structure, the single-layer porous adsorption network can maximize the surface area of the hydrogel-hygroscopic salt composite material in contact with the air compared to the three-dimensional porous adsorption material.
[0051] Here, "the mesh always remains connected" means that the mesh remains connected in the process before moisture absorption until the equilibrium adsorption amount is reached. The mesh remains connected, which can provide sufficient volume expansion space for the hydrogel-hygroscopic salt composite material during moisture absorption and swelling, and avoid agglomeration and stacking to the greatest extent, resulting in a reduction in contact area with the air.
[0052] In the first prior art solution, firstly, the polymerization reaction is carried out in a hygroscopic salt solution, which not only leads to a decrease in the polymerization reaction conversion rate, but also makes it more difficult to purify the polymerized hydrogel, so that toxic crosslinkers, initiators, and monomers remain in the hygroscopic material, resulting in volatilization into the air during the desorption process, affecting human health. Secondly, the hydrogel with hygroscopic salt is coated on the solar panel to form a single-layer structure, which is far less than the specific surface area coated on the mesh structure. Therefore, its adsorption rate is also far lower than the technical solution of the present application.
[0053] In the second prior art solution, the pile fabric is placed in a solvent for polymerization reaction. Since various monomers are soluble in the solvent, they will penetrate into various microstructures of the pile fabric. After the polymerization reaction, the polymer is also filled into all the microstructures of the pile fabric, so that during the process of moisture absorption and swelling, the outer layer of hydrogel swells and blocks the channels formed by the pile fabric, hindering the contact between the hydrogel attached to the inner layer structure and the air. As a result, the process of reaching the equilibrium adsorption amount is particularly long, and the adsorption rate is far lower than the technical solution of the present application.
[0054] In summary, in the present application, the single-layer mesh structure of the porous adsorption net, the hydrophilicity of the porous adsorption net, the use of ionic hydrogel in the hydrogel, and the hydrogel-hygroscopic salt composite material to coat the grid lines of the porous adsorption net are organically combined and support each other, so that the mesh holes can always remain connected, thereby allowing the porous hygroscopic material of the present application to have an extremely high adsorption rate. Specifically, the single-layer mesh structure of the porous adsorption net increases the contact area between the porous adsorption net and the hydrogel-hygroscopic salt composite material and the contact area between the hydrogel-hygroscopic salt composite material and the air. The hydrophilic porous adsorption net has a binding force on the hydrogel-hygroscopic salt composite material to prevent the hydrogel-hygroscopic salt composite material from agglomerating. The ionic hydrogel is bonded to the hygroscopic salt through a valence bond to make the hygroscopic salt less likely to leak and crystallize. Therefore, these technical means have made important contributions to keeping the mesh holes connected.
[0055] The porous hygroscopic material defined in the first technical solution has a higher equilibrium adsorption capacity than the first prior art and the second prior art in most cases, especially when the properties of the hydrogel are the same. The reason is that the specific surface area of the hydrogel-hygroscopic salt composite material in the first technical solution is higher, so that the mass ratio of the substance that can be fully swelled is larger.
[0056] Another important technical effect of using the porous hygroscopic material defined in the first technical solution is that after multiple adsorption-desorption cycles, the hydrogel-hygroscopic salt composite material is less likely to agglomerate than the prior art, and the hygroscopic salt is less likely to leak and crystallize than the prior art. Therefore, its effective service life is longer and does not need to be replaced frequently.
[0057] At the same time, it should be noted that under the existing technical conditions, the preparation method of the porous hygroscopic material defined in the first technical solution can only be achieved by the preparation method defined in the twenty-sixth technical solution. The preparation method defined in the twenty-sixth technical solution is completely different from the first prior art and the second prior art. First, compared with the first prior art, the polymerization reaction is not carried out in a hygroscopic salt solution, so it is easier to purify, and it is not easy for toxic substances to volatilize into the air during the adsorption-desorption cycle. At the same time, the conversion rate is higher and the efficiency of the polymerization reaction is higher. Secondly, compared with the second prior art, the porous adsorption net is not immersed in the solvent during the polymerization reaction stage, so it is possible to keep the mesh holes connected all the time. The most critical thing is that in step 2, the hydrogel is directly swollen in the hygroscopic salt solution and then mechanically crushed to form a micron-sized hydrogel-hygroscopic salt coating, which not only reduces the particle size of the hydrogel-hygroscopic salt to the micron level, but also allows the hygroscopic salt to be more evenly dispersed in the hydrogel, so that the valence bond between the hygroscopic salt and the ions in the hydrogel is more fully bonded. Here, "micrometer-level" means that the particle size of the hydrogel-hygroscopic salt is mostly distributed between 0.1 micrometers and 10 micrometers, among which the part between 0.1 micrometers and 1 micrometer is the main part. In step 3, the micrometer-level hydrogel-hygroscopic salt coating obtained in step 2 is applied to the porous adsorption net to achieve the porous hygroscopic material defined in the first technical solution. Therefore, the porous hygroscopic material defined in the first technical solution cannot be prepared by the preparation methods in the first prior art and the second prior art.
[0058] It can be seen from this that the first technical solution is not achieved by changing the solar panel in the first prior art into a porous adsorption net with a hydrophilic single-layer mesh structure. The first technical solution is also not achieved by changing the three-dimensional pile fabric in the second prior art into a single-layer mesh structure or the "2D structure" referred to in the second prior art, and changing the hydrogel into an ionic hydrogel. In fact, more importantly, the first prior art and the second prior art do not pursue the indicator of adsorption rate. Since the above two prior arts both adopt technical means to achieve desorption through sunlight, they only need to carry out one adsorption-desorption cycle in a day and night. In the present application, the adsorption-desorption cycle is generally completed within half an hour, and at most within one and a half hours, so that dozens of adsorption-desorption cycles can be carried out in a day and night, and its efficiency of moisture absorption and water collection is self-evident.
[0059] In order to better understand the difference and effect between the preparation method defined in the twenty-sixth technical solution and the prior art, reference may be made to the prior art document Hygroscopic-Microgels-Enabled Rapid Water Extractionfrom Arid Air (hygroscopic microgels can quickly extract water from low-humidity air), which is published in advanced materials in 2022. The technical solution of this technical document is to obtain a micron-sized hydrogel by stirring during the polymerization reaction, and then place the micron-sized hydrogel in a hygroscopic salt solution and dry it to obtain a powdered micron-sized hydrogel-hygroscopic salt composite material, and finally spread the micron-sized hydrogel-hygroscopic salt composite material on a single-layer adsorption bed to obtain a hygroscopic material. Of course, even if a porous adsorption net is used for the adsorption bed obtained by this preparation method, the hydrogel-hygroscopic salt composite material cannot cover the grid of the porous adsorption net. In fact, the hygroscopic material obtained by this preparation method is not well combined with the micron-sized hydrogel-hygroscopic salt composite material, and it is easy to cause stacking and agglomeration after multiple adsorption-desorption cycles. Of course, this hygroscopic material has one of the best hygroscopic effects in the literature known to the applicant for single adsorption. Under a relative humidity of 30%, the hygroscopic material has an equilibrium adsorption capacity of 0.8 grams of water per gram of hygroscopic material, and the time to reach 80% equilibrium adsorption capacity is about 20 minutes, and the adsorption rate reaches 1.92Lkg -1 h -1 However, its adsorption rate is still significantly lower than that of the present application.
[0060] The second technical solution is a preferred solution of the first technical solution. The mesh ratio that is always connected is greater than 60%, which can ensure a larger specific surface area and is conducive to balancing the adsorption capacity and improving the moisture absorption efficiency.
[0061] In the third and fourth technical solutions, if the mesh number of the porous adsorption net is greater than 300 meshes, it is easy to reduce the ratio of mesh holes that are always connected. If the mesh number of the porous adsorption net is less than 100 meshes, the absolute amount of water that can be adsorbed by the porous adsorption net per unit area will decrease. Therefore, the mesh number of the porous adsorption net is between 100 mesh and 300 meshes, especially 200 meshes, which is a better embodiment.
[0062] The fifth technical solution provides a preferred implementation of a material for a porous adsorption net that is hydrophilic and capable of being woven.
[0063] In the sixth and seventh technical solutions, if the mass percentage of the hygroscopic salt in the hydrogel-hygroscopic salt composite material is greater than 70%, the hygroscopic salt is prone to leakage after absorbing moisture. If the mass percentage of the hygroscopic salt in the hydrogel-hygroscopic salt composite material is less than 20%, not only will the equilibrium adsorption amount be reduced, but the hydrogel-hygroscopic salt composite material will be too thick and more likely to block holes when applied to the porous adsorption net. If the hygroscopic material is required to achieve a higher equilibrium adsorption amount, the mass percentage of the hygroscopic salt in the hydrogel-hygroscopic salt composite material is preferably greater than 35%.
[0064] The eighth and ninth technical solutions provide preferred options for hygroscopic salts, among which lithium chloride has a better equilibrium adsorption capacity.
[0065] The tenth to thirteenth technical solutions are respectively two cases where the hydrogel contains cations and anions, and preferred options are given.
[0066] In the fourteenth and fifteenth technical solutions, the hydrogel contains both cations and anions. Through the valence bond bonding between the cations in the hydrogel and the anions of the hygroscopic salt and the valence bond bonding between the anions in the hydrogel and the cations of the hygroscopic salt, the hydrogel can have a stronger salt-carrying capacity, and the hygroscopic salt is less likely to leak and crystallize, thereby ensuring a larger equilibrium adsorption amount and a higher adsorption rate.
[0067] The porous hygroscopic material defined in the sixteenth technical solution enables the hydrogel to be prepared by front-end polymerization through the selection of anions and cations, thereby reducing the energy consumption in the preparation process of the hydrogel. The "front-end polymerization" here refers to a polymerization reaction that requires additional energy in the startup stage of the polymerization reaction but does not require additional energy in the maintenance stage of the polymerization reaction.
[0068] The seventeenth technical solution supports the porous hygroscopic material through a support member, so that the porous adsorption net can maintain a single-layer shape and avoid curling or changing shape after absorbing moisture.
[0069] In the eighteenth technical solution, the porous hygroscopic material is planar and there are at least two of them. Each porous hygroscopic material is spaced apart in a direction perpendicular to the plane to form a multi-layer planar structure, which can increase the overall water adsorption capacity of the porous hygroscopic component. At the same time, it is easy to utilize the intervals between each layer of the porous hygroscopic material to maintain the specific surface area of the porous hygroscopic material, and is beneficial to accelerate the desorption efficiency through hot air flow, thereby shortening the time used for the adsorption-desorption cycle.
[0070] In the nineteenth technical solution, the moisture in the air is adsorbed by a porous moisture-absorbing member, desorption is achieved by a heater, and water vapor is converted into liquid water by a condenser, thereby achieving a dehumidification function.
[0071] In the twentieth technical solution, water is collected by a water collector connected to the condenser, so that the dehumidifier has a water collection function.
[0072] In the twenty-first technical solution, a fan is used to make the heated air form convection to achieve desorption more quickly.
[0073] In the twenty-second technical solution, the porous hygroscopic material is arranged in a vertical direction so that the heated air flow can easily carry the water vapor upward, thereby desorbing it more quickly.
[0074] In the twenty-third technical solution, automatic adsorption and desorption are achieved by automatically controlling the opening and closing of the heater.
[0075] The twenty-fourth and twenty-fifth technical solutions are two specific implementation methods of the twenty-third technical solution.
[0076] In the twenty-seventh and twenty-eighth technical solutions, if the mass ratio of the hydrogel to the aqueous solution of the hygroscopic salt is too small, there will be too little hydrogel, and the viscosity of the crushed hydrogel-hygroscopic salt coating will be too low, making it difficult to adhere to the porous adsorption net; if the mass ratio of the hydrogel to the aqueous solution of the hygroscopic salt is too large, the hydrogel-hygroscopic salt coating will be too viscous, making it more likely to produce stacking or pore clogging when applied to the porous adsorption net, thereby reducing the specific surface area.
[0077] In the twenty-seventh and twenty-eighth technical solutions, if the molar ratio of the hygroscopic salt in the aqueous solution of the hygroscopic salt is too small, the equilibrium adsorption capacity of the porous hygroscopic material is likely to decrease. If the molar ratio of the hygroscopic salt in the aqueous solution of the hygroscopic salt is too large, the hygroscopic salt in the porous hygroscopic material is likely to leak, crystallize and agglomerate.
[0078] The twenty-ninth technical solution is a preferred implementation method of mechanical crushing in the twenty-sixth technical solution.
[0079] The 30th and 31st technical solutions show an optional implementation method of coating the hydrogel-hygroscopic salt coating on the porous adsorption network, wherein dip coating can achieve the coating of the hydrogel-hygroscopic salt composite material on the grid by one dipping, and therefore is preferred.
[0080] In the thirty-second technical solution, the cationic group is a quaternary ammonium salt cationic group and the anionic group is a carboxyl group and / or a carboxylate group; and the cross-linking agent and the initiator are both hydrophilic and the first monomer and the second monomer are monomers containing carbon-carbon double bonds and the first solvent is water or a hydrophilic alcohol, then polymerization can be achieved through a front-end polymerization reaction, thereby reducing energy consumption.
[0081] The thirty-third technical solution is a preferred solution of the cross-linking agent, the initiator, the first monomer and the second monomer.
[0082] In the thirty-fourth technical solution, if the molar ratio of the second monomer to the first monomer is greater than 5 to 3, the hygroscopic salt is prone to leakage.
[0083] The thirty-fifth technical solution is a more preferred molar ratio of the thirty-fourth technical solution.
[0084] The thirty-sixth technical solution is an optional technical solution, which represents the thirty-second technical solution and allows monomers without ionic groups to participate in the polymerization reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0085] In order to more clearly illustrate the technical solution of the embodiment, the following briefly introduces the drawings required for use:
[0086] Figure 1 This is a scanning electron microscope photograph of the porous hygroscopic material in Example 1 in a dry state;
[0087] Figure 2 is the adsorption-desorption curve of the porous hygroscopic material in Example 1 at 30% relative humidity;
[0088] Figure 3 It is a structural schematic diagram of the moisture absorption device in Example 1;
[0089] Figure 4 This is a schematic diagram of the structure of the porous moisture-absorbing member in Example 1;
[0090] Figure 5 It is a structural schematic diagram of the moisture absorption device in Example 2;
[0091] Figure 6 This is a scanning electron microscope photograph of the porous hygroscopic material in Example 3 in a dry state;
[0092] Figure 7 This is a scanning electron microscope photograph of the porous hygroscopic material in Example 4 in a dry state;
[0093] Figure 8 This is a metallographic microscope photograph of the porous hygroscopic material in Example 4 after reaching adsorption equilibrium.
[0094] Description of main reference numerals:
[0095] 1. Porous hygroscopic component; 2. Gravimeter; 3. Fan; 4. Heater; 5. Wind hood; 6. Condenser; 7. Water collector; 8. Shell; 9. Door; 10. Door driver; 11. Controller; 12. Bracket; 13. Porous hygroscopic material; 14. Lower frame; 15. Upper frame; 16. Support column; 17. Air hole; 18. Hygrometer. DETAILED DESCRIPTION
[0096] In the claims and the description, unless otherwise defined, the terms "first", "second" or "third", etc. are intended to distinguish different objects rather than to describe a specific order.
[0097] In the claims and the specification, unless otherwise defined, terms such as "center", "lateral", "longitudinal", "horizontal", "vertical", "top", "bottom", "inside", "outside", "up", "down", "front", "back", "left", "right", "clockwise", "counterclockwise" and the like indicating directions or positional relationships are based on the directions and positional relationships shown in the drawings and are only for the convenience of simplifying the description and do not imply that the device or element referred to must have a specific direction or be constructed and operated in a specific direction.
[0098] In the claims and the specification, unless otherwise defined, the term "fixed connection" or "fixed connection" should be understood in a broad sense, that is, any connection method in which there is no displacement relationship and relative rotation relationship between the two parties, that is to say, including non-detachable fixed connection, detachable fixed connection, integral connection and fixed connection through other devices or elements.
[0099] In the claims and the description, unless otherwise defined, the terms "includes", "has" and their variations mean "including but not limited to".
[0100] In the claims and the specification, unless otherwise defined, the term "provided with" means that the technical feature located thereafter is a part of the technical feature located therefor.
[0101] In the claims and description, unless otherwise defined, the term "encapsulating" means that the hydrogel-hygroscopic salt composite material three-dimensionally encapsulates the grid lines of the single-layer porous adsorbent network.
[0102] In the claims and the specification, unless otherwise specified, the term "the mesh holes remain connected all the time" means that the mesh holes remain connected all the time during the process before moisture absorption until the equilibrium adsorption amount is reached.
[0103] In the claims and description, unless otherwise defined, the term "micrometer-sized" means that the particle sizes of the hydrogel-hygroscopic salt in water are mostly distributed between 0.1 micrometers and 10 micrometers, among which the part between 0.1 micrometers and 1 micrometer is the main part.
[0104] In the claims and the specification, unless otherwise defined, the term "front-end polymerization reaction" refers to a polymerization reaction that requires additional energy to be provided in the startup stage of the polymerization reaction but does not require additional energy to be provided in the maintenance stage of the polymerization reaction.
[0105] In the claims and description, unless otherwise defined, the term "equilibrium adsorption capacity" refers to the number of grams of water adsorbed by each gram of the hydrogel-hygroscopic salt composite material when the adsorption capacity of the porous hygroscopic material reaches equilibrium, and the unit is g / g (gram / gram).
[0106] In the claims and description, unless otherwise defined, the term "adsorption time" refers to the time required for the adsorption amount of the porous hygroscopic material to increase from 0% to 80% of the equilibrium adsorption amount, and the unit in this application is min or h (minutes or hours).
[0107] In the claims and specification, unless otherwise defined, the term "desorption time" refers to the time required for the adsorption amount of the porous hygroscopic material to desorb from 80% of the equilibrium adsorption amount to 0, and the unit in this application is min or h (minutes or hours).
[0108] In the claims and description, unless otherwise specified, the term "adsorption rate" refers to the volume of water adsorbed per kilogram of hydrogel-hygroscopic salt composite material per hour, in units of Lkg -1 h -1 (liters per kilogram per hour), which is specifically calculated by dividing the volume of water corresponding to the adsorption of the porous hygroscopic material from 0 to 80% equilibrium adsorption by the adsorption time and then by the mass of the hydrogel-hygroscopic salt composite material.
[0109] In the claims and description, unless otherwise specified, the term "desorption rate" refers to the volume of water desorbed per kilogram of hydrogel-hygroscopic salt composite material per hour, in units of Lkg -1 h -1 (liters per kilogram per hour), which is specifically calculated by dividing the volume of water corresponding to the desorption of the porous hygroscopic material from 80% of the equilibrium adsorption to 0 by the desorption time and then by the mass of the hydrogel-hygroscopic salt composite material.
[0110] The technical solutions in the embodiments will be described clearly and completely below in conjunction with the accompanying drawings.
[0111] Embodiment 1
[0112] 1. Preparation of hydrogel
[0113] The hydrogel in Example 1 is prepared by free radical polymerization of a first monomer containing a quaternary ammonium salt cationic group and a second monomer containing a carboxyl anionic group, a crosslinker and an initiator under the condition of a first solvent, and then purified and dried. Among them, the free radical polymerization reaction is a front-end polymerization reaction, the crosslinker and the initiator are both hydrophilic, the first monomer and the second monomer are monomers containing carbon-carbon double bonds, and the first solvent is water or hydrophilic alcohols. The "front-end polymerization reaction" here refers to a polymerization reaction that requires additional energy in the startup stage of the polymerization reaction, but does not require additional energy in the maintenance stage of the polymerization reaction. Specifically, in this embodiment, the first monomer is acryloyloxyethyl trimethylammonium chloride, and (3-acrylamide propyl) trimethylammonium chloride can also be used in other embodiments; the second monomer is acrylic acid, the crosslinker is an acrylamide crosslinker, specifically N, N-methylenebisacrylamide; the initiator is a peroxide or azo initiator, specifically ammonium persulfate; the first solvent is water.
[0114] The specific preparation process is as follows:
[0115] 0.013 g of N,N-dimethylbisacrylamide was dissolved in 0.5 g of acrylic acid by stirring at room temperature / manual shaking, and then 4.66 g of acryloyloxyethyltrimethylammonium chloride (80 wt % aqueous solution) was added and stirred at room temperature / manually shaken to dissolve, which was marked as solution A;
[0116] Prepare an aqueous solution of ammonium persulfate: add 0.041 g of ammonium persulfate to 0.082 g of water, stir at room temperature / shake manually to dissolve, and mark it as solution B;
[0117] Add solution B to solution A, stir at room temperature / shake manually to dissolve, and mark it as solution C;
[0118] Add solution C to a glass test tube with a diameter of 1.5 cm and a height of 20 cm;
[0119] Heat the tube wall with a 300℃ soldering iron until the polymerization reaction starts, then remove the soldering iron to allow the polymerization reaction to proceed spontaneously until completion;
[0120] After the polymerization reaction is completed, the mixture is added into water until it is completely swollen and then taken out. Anhydrous ethanol is then added three times to wash away the unreacted reactants for purification. The polymer is placed in an oven at 80°C and dried for 12 hours to obtain a hydrogel.
[0121] In this embodiment, the molar ratio of the second monomer to the first monomer is 1:3.
[0122] The prepared hydrogel is in the form of porous fragments and is easy to break. The prepared hydrogel contains cations and anions, the cations are quaternary ammonium cations, and the anions are carboxyl groups.
[0123] 2. Preparation of porous hygroscopic materials
[0124] The process of preparing porous hygroscopic materials mainly includes:
[0125] Step 1: placing the hydrogel in an aqueous solution of a hygroscopic salt;
[0126] Step 2: After the hydrogel swells, it is mechanically crushed to form a micron-sized hydrogel-hygroscopic salt coating; and
[0127] Step 3: Apply the hydrogel-hygroscopic salt coating to a hydrophilic and monolayer porous adsorption network and dry it.
[0128] Wherein, in step 1, the hygroscopic salt is one or more of lithium chloride, calcium chloride, magnesium chloride and lithium bromide, preferably lithium chloride; the mass ratio of the hydrogel to the aqueous solution of the hygroscopic salt is between 1:40 and 1:20; in the aqueous solution of the hygroscopic salt, the molar ratio of the hygroscopic salt is between 0.5 mol / L and 3 mol / L. Preferably, the mass ratio of the hydrogel to the aqueous solution of the hygroscopic salt is preferably between 1:25 and 1:35; in the aqueous solution of the hygroscopic salt, the molar ratio of the hygroscopic salt is preferably between 1 mol / L and 2 mol / L.
[0129] In step 2, mechanical disruption is performed by stirring.
[0130] In step 3, the mesh size of the porous adsorption net is between 100 mesh and 300 mesh, preferably 200 mesh, and the material of the porous adsorption net is preferably nylon or polyurethane or glass or silicon carbide; the method of coating the hydrogel-hygroscopic salt coating on the porous adsorption net includes dip coating, spray coating, brush coating, rod coating, and spin coating, preferably dip coating.
[0131] Specifically in this embodiment, in step 1, the hygroscopic salt is lithium chloride; the molar ratio of the hygroscopic salt in the hygroscopic salt solution is 1 mol / L; the mass ratio of the hydrogel to the hygroscopic salt solution is 1 to 30. In step 2, the stirring speed is 12000 r / min (revolutions per minute). In step 3, the mesh number of the porous adsorption net is 200 mesh, the material of the porous adsorption net is nylon, and the method of applying the hydrogel-hygroscopic salt coating to the porous adsorption net is dip coating.
[0132] The specific preparation process is as follows:
[0133] Take 4.239g lithium chloride and add it to 10g deionized water. Stir at room temperature / shake manually to dissolve. Then transfer it to a 250ml measuring cylinder and continue to add deionized water until 100ml is obtained to prepare a 1mol / L lithium chloride aqueous solution, that is, 42.39g lithium chloride in 1000ml salt solution.
[0134] Take 1g of the prepared hydrogel and add it to 30g of the prepared lithium chloride aqueous solution, and leave it for 12h to wait for it to swell completely;
[0135] The fully swollen hydrogel-lithium chloride mixed solution was crushed by a homogenizer at 12,000 revolutions for 4 minutes to obtain an ionic hydrogel-lithium chloride coating with a particle size of micrometers. Here, "micrometers" means that the particle size of the hydrogel-hygroscopic salt is mostly distributed between 0.1 micrometers and 10 micrometers, among which the part between 0.1 micrometers and 1 micrometer is the main part.
[0136] A 200-mesh single-layer porous nylon mesh with a length and width of 6.5 cm was immersed in the prepared ionic hydrogel-lithium chloride aqueous solution coating, and then immediately taken out and placed in a 110° C. oven for drying for 30 minutes; thus, the porous hygroscopic material in this embodiment was obtained.
[0137] 3. Structure of porous hygroscopic materials
[0138] See also Figure 1 , Figure 1 The structure of the porous hygroscopic material in the first embodiment in a dry state is shown. Figure 1 As shown, the porous hygroscopic material includes a porous adsorption net and a hydrogel-hygroscopic salt composite material. Among them, the porous adsorption net is in a single-layer mesh shape and the material is hydrophilic. The hydrogel-hygroscopic salt composite material covers at least part of the network lines of the porous adsorption net and keeps at least part of the mesh holes connected. The hydrogel-hygroscopic salt composite material includes a hydrogel and a hygroscopic salt that are integrated with each other, and the hydrogel is an ionic hydrogel. The "coating" here means that the hydrogel-hygroscopic salt composite material three-dimensionally covers the grid lines of the single-layer porous adsorption net.
[0139] Specifically in this embodiment, the porous adsorption net in the porous hygroscopic material is a single-layer nylon net with a mesh size of 200. In the portion where the hydrogel-hygroscopic salt composite material is adhered to the porous adsorption net, the hydrogel-hygroscopic salt composite material covers the grid lines of the porous adsorption net, and the number of mesh holes that are maintained through accounts for greater than or equal to 60%.
[0140] 4. Adsorption and desorption curves of porous hygroscopic materials
[0141] In the present application, “equilibrium adsorption capacity” refers to the number of grams of water adsorbed by each gram of hydrogel-hygroscopic salt composite material when the adsorption capacity of the porous hygroscopic material reaches equilibrium, and the unit is g / g (gram / gram). “Adsorption time” refers to the time required for the adsorption capacity of the porous hygroscopic material to be adsorbed from 0 to 80% of the equilibrium adsorption capacity, and the unit in the present application is min or h (minutes or hours). “Desorption time” refers to the time required for the adsorption capacity of the porous hygroscopic material to be desorbed from 80% of the equilibrium adsorption capacity to 0, and the unit in the present application is min or h (minutes or hours). “Adsorption rate” refers to the volume of water adsorbed per kilogram of hydrogel-hygroscopic salt composite material per hour, and the unit is Lkg -1 h -1(liters per kilogram per hour), which is calculated by dividing the volume of water corresponding to the adsorption of the porous hygroscopic material from 0% to 80% of the equilibrium adsorption by the adsorption time and then by the mass of the hydrogel-hygroscopic salt composite material. "Desorption rate" refers to the volume of water desorbed per kilogram of hydrogel-hygroscopic salt composite material per hour, and the unit is Lkg -1 h -1 (liters per kilogram per hour), which is specifically calculated by dividing the volume of water corresponding to the desorption of the porous hygroscopic material from 80% of the equilibrium adsorption to 0 by the desorption time and then by the mass of the hydrogel-hygroscopic salt composite material.
[0142] The specific method for measuring adsorption and desorption curves is as follows:
[0143] The porous hygroscopic material was placed in a constant temperature and humidity chamber (temperature 25°C, relative humidity 30% or 60%). The porous hygroscopic material was then heated on a hot plate at 110°C for 30 minutes, and then quickly transferred to an electronic balance with an accuracy of 0.1 mg for weighing; the electronic balance was used for automatic data recording and reading, with a reading interval of 5 seconds, to test its adsorption curve;
[0144] The sample that has reached adsorption equilibrium is placed on a hot plate at 70°C for heating. The sample is taken out every 1 minute and weighed using an electronic balance for 30 minutes to test its desorption curve.
[0145] See also Figure 2 , Figure 2 FIG. 2 shows the adsorption-desorption curve of the porous hygroscopic material in Example 1 at 30% relative humidity. Figure 2 As shown, at 30% relative humidity, the porous hygroscopic material equilibrium adsorption capacity of this embodiment is 0.92g / g, the adsorption time is 12.98min, the desorption time is 9.99min, and the adsorption rate is 3.4Lkg -1 h -1 , the desorption rate is 4.42Lkg -1 h -1 .
[0146] After testing, at a relative humidity of 60%, the porous hygroscopic material equilibrium adsorption capacity of this embodiment is 1.56g / g, and the adsorption rate is 4.7Lkg -1 h -1 , the desorption rate is 5.4Lkg -1 h -1 .
[0147] 5. Dehumidification device and porous adsorbent
[0148] See also Figure 3 , Figure 3 FIG. 2 shows the dehumidification device in this embodiment. Figure 3 As shown, in this embodiment, the dehumidification device includes a porous moisture absorbing element 1, a gravimeter 2, a fan 3, a heater 4, an air collecting hood 5, a condenser 6, a water collector 7, a shell 8, a door 9, a door drive 10 and a controller 11.
[0149] See also Figure 4 , Figure 4 The porous moisture-absorbing member 1 in this embodiment is shown. Figure 4 As shown, the porous hygroscopic member 1 in this embodiment includes a bracket 12 and a porous hygroscopic material 13 in this embodiment, wherein the bracket 12 is used to support the porous hygroscopic material 13. In this embodiment, the porous hygroscopic material 13 is planar, and the number of the porous hygroscopic materials 13 is at least two, specifically 5. Of course, the number of the porous hygroscopic material 13 can also be 1. Each porous hygroscopic material 13 is arranged at intervals along a direction perpendicular to the plane. In this embodiment, the porous hygroscopic material 13 is arranged vertically. The bracket 12 includes a lower frame 14, an upper frame 15 and a support 16 fixed to each other. The support 16 is arranged in a four-corner layout, and is used to connect the lower frame 14 and the upper frame 15. The lower frame 14 and the upper frame 15 are used to tension and support each porous hygroscopic material 13, respectively. The lower frame 14 and the upper frame 15 are both provided with a plurality of air holes 17 . The air holes 17 are arranged parallel to the porous hygroscopic materials 13 . Both sides of each porous hygroscopic material 13 are provided with air holes 17 .
[0150] like Figure 3As shown, the gravimeter 2 is used to support the porous hygroscopic member 1 and to detect the weight of the porous hygroscopic member 1 to characterize the amount of water adsorbed by the porous hygroscopic material 13. The fan 3 is located below the porous hygroscopic member 1 and is used to form convection of the air heated by the heater 4 to desorb the porous hygroscopic material 13 on the porous hygroscopic member 1. In this embodiment, the heated airflow formed by the fan 3 passes upward through each air hole 17 and each porous hygroscopic material 13. The heater 4 desorbs the porous hygroscopic material 13 on the porous hygroscopic member 1 by heating. In this embodiment, the heater 4 is arranged below the fan 3. The air collecting hood 5 is arranged above the porous hygroscopic member 1 to collect hot water vapor formed by desorption of the porous hygroscopic material 13. The condenser 6 is connected to the air collecting hood 5 to form condensed water from the water vapor formed after the porous hygroscopic material 13 is desorbed. The water collector 7 is connected to the condenser 6 to collect the condensed water generated by the condenser 6. The housing 8 accommodates the porous hygroscopic member 1, the gravimeter 2, the fan 3, the heater 4, the wind collecting cover 5, the condenser 6 and the water collector 7. The housing 8 is provided with an opening. The door 9 is arranged at the opening for closing or opening the opening. The door driver 10 is used to drive the door 9 to close or open the opening. The controller 11 is accommodated in the housing 8. The controller 11 is electrically connected to the gravimeter 2, the fan 3, the heater 4 and the door driver 10 respectively. The fan 3, the heater 4 and the door driver 10 are controlled to open and close according to the amount of water adsorbed by the porous hygroscopic material 13 represented by the weight of the porous hygroscopic member 1 detected by the gravimeter 2.
[0151] Specifically, when the amount of water adsorbed by the porous hygroscopic material 13 reaches or exceeds the first threshold, the controller 11 controls the door driver 10 to close the opening of the housing 8 by the door 9, and controls the fan 3 and the heater 4 to start to achieve desorption of the porous hygroscopic material 13; when the amount of water adsorbed by the porous hygroscopic material 13 reaches or falls below the second threshold, the controller 11 controls the door driver 10 to open the opening of the housing 8 by the door 9, and controls the fan 3 and the heater 4 to shut down to achieve adsorption of the porous hygroscopic material 10. Thus, the dehumidification device achieves an automatic adsorption-desorption cycle.
[0152] Embodiment 2
[0153] The difference between the second embodiment and the first embodiment lies in the structure of the dehumidification device. The rest of the parts are the same as the first embodiment.
[0154] See also Figure 5 , Figure 5 The dehumidification device in the second embodiment is shown. Figure 5 As shown, the dehumidification device in the second embodiment is different from the first embodiment in that the dehumidification device in the second embodiment no longer has the gravimeter 2 in the first embodiment, but has a hygrometer 18 fixed to the housing 8 and extending out of the housing 8. The controller 11 is also connected to the hygrometer 18 via electrical signals.
[0155] The hygrometer 18 is used to detect the ambient humidity. The controller 11 characterizes the amount of water adsorbed by the porous hygroscopic material 13 according to the period after the heater 4 is turned off and the period after it is turned on, based on the ambient humidity detected by the hygrometer 18. Similarly, when the amount of water adsorbed by the porous hygroscopic material 13 reaches or exceeds the first threshold, the controller 11 controls the door driver 10 to close the opening of the housing 8, and controls the fan 3 and the heater 4 to start to achieve desorption of the porous hygroscopic material 13; when the amount of water adsorbed by the porous hygroscopic material 13 reaches or falls below the second threshold, the controller 11 controls the door driver 10 to open the opening of the housing 8, and controls the fan 3 and the heater 4 to turn off to achieve adsorption of the porous hygroscopic material 10.
[0156] The rest of the dehumidification device in the second embodiment is the same as that in the first embodiment.
[0157] Embodiment 3
[0158] The difference between the third embodiment and the first embodiment is that the mesh number of the porous adsorption net is 100. The rest of the fourth embodiment is the same as the first embodiment.
[0159] See also Figure 6 , Figure 6 The structure of the porous hygroscopic material in the fourth embodiment in a dry state is shown. Figure 6 As shown, when the mesh number of the porous adsorption net reaches 100 meshes, in the portion of the grid line of the porous adsorption net covered by the hydrogel-hygroscopic salt composite material, the number of mesh holes that always remain through accounts for greater than or equal to 60%.
[0160] Embodiment 4
[0161] The difference between Example 4 and Example 1 is that when preparing the porous hygroscopic material, the molar ratio of the hygroscopic salt in the hygroscopic salt solution is 0.5 mol / L; the mass ratio of the hydrogel to the hygroscopic salt solution is 1 to 20, so that in the prepared porous hygroscopic material, the mass percentage of the hygroscopic salt in the hydrogel-hygroscopic salt composite material is 35%. The mesh number of the porous adsorption net in Example 4 is 300 meshes. The rest of Example 5 is the same as Example 1.
[0162] See also Figure 7 and Figure 8 , Figure 7 The structure of the porous hygroscopic material in the fourth embodiment in a dry state is shown. Figure 8 The structure of the porous hygroscopic material in Example 5 after reaching adsorption equilibrium is shown. Figure 7 As shown, in Example 5, in the portion of the grid lines of the porous adsorption net covered by the hydrogel-hygroscopic salt composite material, the number of mesh holes that remain through in the dry state is also greater than or equal to 60%. Figure 8As shown, in Example 5, in the part of the grid line of the porous adsorption net coated with the hydrogel-hygroscopic salt composite material, the number of mesh holes that remain connected after reaching adsorption equilibrium does not change significantly, and is still greater than or equal to 60%. Since in Example 4, the mass percentage of hygroscopic salt in the hydrogel-hygroscopic salt composite material is not high, it means that the hydrogel accounts for a high proportion, the hydrogel-hygroscopic salt composite material is relatively viscous, and the mesh number of the porous adsorption net is 300 meshes, therefore, in Example 4, the number of mesh holes that remain connected after the porous hygroscopic material reaches adsorption equilibrium can still reach or be equal to 60%, which means that in each embodiment, the porous hygroscopic material can always keep the mesh holes connected during the process from before adsorption to adsorption equilibrium.
[0163] The porous hygroscopic material in Example 4 has an equilibrium adsorption capacity of 0.65 g / g at 30% relative humidity, an adsorption time of 6.95 min, a desorption time of 6.47 min, and an adsorption rate of 3.9 L / kg -1 h -1 , the desorption rate is 4.8Lkg -1 h -1 .
[0164] The rest of the fourth embodiment is the same as the first embodiment.
[0165] Embodiment 5
[0166] The difference between Example 5 and Example 1 is that when preparing the porous hygroscopic material, the molar ratio of the hygroscopic salt in the hygroscopic salt solution is 3 mol / L; the mass ratio of the hydrogel to the hygroscopic salt solution is 1 to 30, so in the prepared porous hygroscopic material, the mass percentage of the hygroscopic salt in the hydrogel-hygroscopic salt composite material is 70%.
[0167] The porous hygroscopic material in Example 5 has an equilibrium adsorption capacity of 1.52 g / g at 30% relative humidity, an adsorption time of 30.02 min, a desorption time of 23.31 min, and an adsorption rate of 2.4 L / kg -1 h -1 , the desorption rate is 3.1Lkg -1 h -1 .
[0168] The rest of the fifth embodiment is the same as the first embodiment.
[0169] Embodiment 6
[0170] The difference between Example 6 and Example 1 is that when preparing the hydrogel, the second monomer is sodium acrylate, so the anion group in the hydrogel is a carboxylate.
[0171] The porous hygroscopic material in Example 6 has an equilibrium adsorption capacity of 0.9 g / g at 30% relative humidity, an adsorption time of 13.42 min, a desorption time of 10.05 min, and an adsorption rate of 3.2 L / kg -1 h -1 , the desorption rate is 4.3Lkg -1 h -1 .
[0172] The rest of the sixth embodiment is the same as the first embodiment.
[0173] Embodiment 7
[0174] The difference between Example 7 and Example 1 is that when preparing the porous adsorption material, calcium chloride is used as the hygroscopic salt.
[0175] The porous hygroscopic material in Example 7 has an equilibrium adsorption capacity of 0.6 g / g at 30% relative humidity, an adsorption time of 9.82 min, a desorption time of 7.02 min, and an adsorption rate of 2.9 L / kg -1 h -1 , the desorption rate is 4.1Lkg -1 h -1 .
[0176] The rest of the seventh embodiment is the same as the first embodiment.
[0177] Embodiment 8
[0178] The difference between Example 8 and Example 1 is that, when preparing the hydrogel, the molar ratio of the second monomer to the first monomer is 5:3.
[0179] The porous hygroscopic material in Example 8 has an equilibrium adsorption capacity of 0.85 g / g at 30% relative humidity, an adsorption time of 12.1 min, a desorption time of 9.69 min, and an adsorption rate of 3.4 L / kg -1 h -1 , the desorption rate is 4.2Lkg -1 h -1 .
[0180] The rest of the eighth embodiment is the same as the first embodiment.
[0181] Embodiment 9
[0182] The difference between Example 9 and Example 1 is that, when preparing the hydrogel, the molar ratio of the second monomer to the first monomer is 1:5.
[0183] The porous hygroscopic material in Example 9 has an equilibrium adsorption capacity of 0.91 g / g at 30% relative humidity, an adsorption time of 14 min, a desorption time of 10.92 min, and an adsorption rate of 3.1 L / kg.-1 h -1 , the desorption rate is 4.0Lkg -1 h -1 .
[0184] The rest of the ninth embodiment is the same as the first embodiment.
[0185] Embodiment 10
[0186] The difference between Example 10 and Example 1 is that no second monomer is used in the preparation of the hydrogel, so the hydrogel and the hydrogel-hygroscopic salt composite material do not contain anionic groups.
[0187] The porous hygroscopic material in Example 10 has an equilibrium adsorption capacity of 0.8 g / g at 30% relative humidity, an adsorption time of 14.0 min, a desorption time of 10.8 min, and an adsorption rate of 3.1 L / kg -1 h -1 , the desorption rate is 4.0Lkg -1 h -1 .
[0188] The rest of the embodiment 10 is the same as the embodiment 1.
[0189] Embodiment 11
[0190] The difference between Example 11 and Example 1 is that, when preparing the hydrogel, no first monomer is present, so the hydrogel and the hydrogel-hygroscopic salt composite material do not contain cationic groups.
[0191] The porous hygroscopic material in Example 11 has an equilibrium adsorption capacity of 0.8 g / g at 30% relative humidity, an adsorption time of 40.9 min, a desorption time of 32.3 min, and an adsorption rate of 0.9 L / kg -1 h -1 , the desorption rate is 1.2Lkg -1 h -1 .
[0192] The rest of the embodiment eleven is the same as the embodiment one.
[0193] In addition to the above embodiments, in other embodiments, when preparing the hydrogel, the third monomer participating in the free radical polymerization reaction may also be included, and the third monomer is a monomer without an ionic group and containing a carbon-carbon double bond; the third monomer is preferably a monomer of acrylate, methacrylate, acrylamide or methacrylamide.
[0194] In addition to the above embodiments, if the polymerization reaction for preparing the hydrogel is not considered to be a front-end polymerization reaction, the anionic group contained in the second monomer during the preparation of the hydrogel may also be a sulfonate group and / or a phosphate group.
[0195] From the above embodiments, it can be seen that:
[0196] In each embodiment, the hydrogel is an ionic hydrogel, which can form a valence bond with the hygroscopic salt, thereby having a stronger salt-carrying capacity, making the hygroscopic salt less likely to leak or result, and being dispersed in the hydrogel skeleton.
[0197] In each embodiment, the porous adsorption network is hydrophilic and can better combine with the hydrogel-hygroscopic salt composite material, thereby more effectively avoiding the agglomeration of the hydrogel-hygroscopic salt composite material.
[0198] In each embodiment, the hydrogel-hygroscopic salt composite material three-dimensionally covers the grid lines of the single-layer porous adsorption net, which not only enables the hydrogel-hygroscopic salt composite material to obtain the maximum specific surface area, but also enables the hydrophilic porous adsorption net and the hydrogel-hygroscopic salt composite material to have the maximum contact area, thereby more effectively avoiding the agglomeration of the hydrogel-hygroscopic salt composite material. It should be noted that under this structure, the single-layer porous adsorption net can maximize the surface area of the hydrogel-hygroscopic salt composite material in contact with the air compared to the three-dimensional porous adsorption material.
[0199] In each embodiment, the mesh holes are always kept through, which can provide sufficient volume expansion space for the hydrogel-hygroscopic salt composite material during the process of moisture absorption and swelling, and avoid agglomeration and mutual stacking to the greatest extent, resulting in a reduction in the contact area with the air.
[0200] In each embodiment, the single-layer mesh structure of the porous adsorption net, the hydrophilicity of the porous adsorption net, the use of ionic hydrogel in the hydrogel, and the grid lines of the porous adsorption net coated with the hydrogel-hygroscopic salt composite material are organically combined and mutually supported to enable the mesh to always remain connected, so that the porous hygroscopic material of the present application has an extremely high adsorption rate. Specifically, the single-layer mesh structure of the porous adsorption net increases the contact area between the porous adsorption net and the hydrogel-hygroscopic salt composite material and the contact area between the hydrogel-hygroscopic salt composite material and the air. The binding force of the hydrophilic porous adsorption net on the hydrogel-hygroscopic salt composite material prevents the hydrogel-hygroscopic salt composite material from agglomerating. The ionic hydrogel combines with the valence bond of the hygroscopic salt to make the hygroscopic salt less likely to leak and crystallize. Therefore, these technical means are all conducive to keeping the mesh connected at all times.
[0201] In most cases, the equilibrium adsorption capacity of each embodiment is higher than that of the prior art, especially when the properties of the hydrogel are the same. The reason is that the specific surface area of the hydrogel-hygroscopic salt composite material in each embodiment is higher, so that the mass ratio of the substance that can be fully swollen is larger.
[0202] In each embodiment, after multiple adsorption-desorption cycles, the hydrogel-hygroscopic salt composite material is less likely to agglomerate than the prior art, and the hygroscopic salt is less likely to leak and crystallize than the prior art. Therefore, its effective service life is longer and does not need to be frequently replaced.
[0203] The preparation method of the porous hygroscopic material in each embodiment is completely different from the prior art. First, compared with the first prior art, the polymerization reaction is not carried out in a hygroscopic salt solution, so it is easier to purify, and it is not easy to volatilize toxic substances into the air in the adsorption-desorption cycle. At the same time, the conversion rate is higher and the efficiency of the polymerization reaction is higher. Secondly, compared with the second prior art, the porous adsorption net is not immersed in the solvent during the polymerization reaction stage, so it is possible to keep the mesh holes connected all the time. The most critical thing is that in step 2, the hydrogel is directly swollen in the hygroscopic salt solution and then mechanically crushed to form a micron-scale hydrogel-hygroscopic salt coating, which not only reduces the particle size of the hydrogel-hygroscopic salt to the micron level, but also allows the hygroscopic salt to be more evenly dispersed in the hydrogel, so that the valence bond between the hygroscopic salt and the ions in the hydrogel is more fully combined. In step 3, the micron-scale hydrogel-hygroscopic salt coating obtained in step 2 is applied to the porous adsorption net, and then the porous hygroscopic material defined in each embodiment can be realized. Therefore, the porous hygroscopic materials of each embodiment cannot be prepared by the preparation methods in the first prior art and the second prior art.
[0204] In each embodiment, the adsorption-desorption cycle is generally completed within half an hour, and at most within one and a half hours, so that dozens of adsorption-desorption cycles can be performed in a day and night, and its efficiency in moisture absorption and water collection is self-evident.
[0205] In each embodiment, the ratio of mesh holes that are always connected is greater than 60%, which can ensure a larger specific surface area and is beneficial to the balance between adsorption capacity and improvement of moisture absorption efficiency.
[0206] In each embodiment, lithium chloride is selected as the hygroscopic salt, and the equilibrium adsorption capacity is better.
[0207] In Examples 1 to 10, the hydrogel can be prepared by front-end polymerization through the selection of anions and cations, thereby reducing the energy consumption in the preparation process of the hydrogel. Here, "front-end polymerization" refers to a polymerization reaction that requires additional energy in the startup stage of the polymerization reaction but does not require additional energy in the maintenance stage of the polymerization reaction.
[0208] In each embodiment, the porous moisture-absorbing material is supported by a support member so that the porous adsorbent net can maintain a single-layer shape and avoid curling or changing shape after absorbing moisture.
[0209] In each embodiment, the porous hygroscopic material is planar and there are at least two of them. Each porous hygroscopic material is spaced apart in a direction perpendicular to the plane to form a multi-layer planar structure, which can increase the overall water adsorption capacity of the porous hygroscopic component. At the same time, it is easy to utilize the intervals between each layer of the porous hygroscopic material to maintain the specific surface area of the porous hygroscopic material, and is beneficial to accelerate the desorption efficiency through hot air flow, thereby shortening the time used for the adsorption-desorption cycle.
[0210] In each embodiment, the moisture in the air is adsorbed by the porous moisture-absorbing element, desorption is achieved by the heater, and the water vapor is converted into liquid water by the condenser, thereby achieving a dehumidification function.
[0211] In each embodiment, the heated air is convected by a fan to achieve desorption more quickly.
[0212] In each embodiment, the porous hygroscopic material is arranged in a vertical direction so that the heated air flow can easily carry the water vapor upward, thereby desorbing it more quickly.
[0213] In each embodiment, automatic adsorption and desorption are achieved by automatically controlling the opening and closing of the heater.
[0214] In each embodiment, the cationic group is a quaternary ammonium salt cationic group and the anionic group is a carboxyl group and / or a carboxylate group; and the cross-linking agent and the initiator are both hydrophilic and the first monomer and the second monomer are monomers containing carbon-carbon double bonds and the first solvent is water or a hydrophilic alcohol, then polymerization can be achieved through a front-end polymerization reaction, thereby reducing energy consumption.
[0215] The above specification and description of the embodiments are used to explain the protection scope of the present application, but do not constitute a limitation on the protection scope of the present application.
Claims
1. A porous hygroscopic material, characterized in that include: The porous adsorption net is in the form of a single-layer net and its material is hydrophilic; and The hydrogel-hygroscopic salt composite material covers at least part of the grid lines of the porous adsorption network and keeps at least part of the mesh holes connected all the time. The hydrogel-hygroscopic salt composite material comprises a hydrogel and a hygroscopic salt integrated with each other, and the hydrogel is an ionic hydrogel.
2. The porous hygroscopic material according to claim 1, characterized in that: In the portion of the hydrogel-hygroscopic salt coated grid lines, the number of mesh holes that always remain through accounts for greater than or equal to 60%.
3. The porous hygroscopic material according to claim 1, characterized in that: The mesh number of the porous adsorption net is between 100 meshes and 300 meshes.
4. The porous hygroscopic material according to claim 3, characterized in that: The mesh size of the porous adsorption net is preferably 200 meshes.
5. The porous hygroscopic material according to claim 1, wherein: The material of the porous adsorption net is preferably nylon, polyurethane, glass or silicon carbide.
6. The porous hygroscopic material according to claim 1, wherein: The mass percentage of the hygroscopic salt in the hydrogel-hygroscopic salt composite material is between 20% and 70%.
7. The porous hygroscopic material according to claim 6, characterized in that: The mass percentage of the hygroscopic salt in the hydrogel-hygroscopic salt composite material is between 35% and 70%.
8. The porous hygroscopic material according to claim 1, wherein: The hygroscopic salt is one or more of lithium chloride, calcium chloride, magnesium chloride and lithium bromide.
9. The porous hygroscopic material according to claim 8, characterized in that: The hygroscopic salt is preferably lithium chloride.
10. The porous hygroscopic material according to any one of claims 1 to 9, characterized in that: The hydrogel contains cations.
11. The porous hygroscopic material according to claim 10, wherein: The cation is preferably a quaternary ammonium cation.
12. The porous hygroscopic material according to any one of claims 1 to 9, characterized in that: The hydrogel contains anions.
13. The porous hygroscopic material according to claim 12, wherein: The anion is preferably one or more of carboxyl, carboxylate, sulfonate and phosphate.
14. The porous hygroscopic material according to any one of claims 1 to 9, characterized in that: The hydrogel contains cations and anions.
15. The porous hygroscopic material according to claim 14, wherein: The cation is preferably a quaternary ammonium cation, and the anion is preferably one or more of a carboxyl group, a carboxylate group, a sulfonate group, and a phosphate group.
16. The porous hygroscopic material according to claim 15, wherein: The anion is more preferably carboxyl and / or carboxylate.
17. A porous moisture-absorbing member, characterized in that: It comprises a support and the porous hygroscopic material according to any one of claims 1 to 16, wherein the support supports the porous hygroscopic material.
18. The porous absorbent member according to claim 17, wherein: The porous hygroscopic material is in a planar shape, the number of the porous hygroscopic materials is at least two, and each porous hygroscopic material is arranged at intervals along a direction perpendicular to its plane.
19. A dehumidification device, characterized in that: It comprises a heater, a condenser and a porous hygroscopic component as claimed in claim 17 or 18; the heater desorbs the porous hygroscopic material on the porous hygroscopic component by heating, and the condenser is used to condense water from the water vapor formed after the porous hygroscopic material is desorbed.
20. The dehumidification device according to claim 19, characterized in that: The utility model further comprises a water collector which is in communication with the condenser to collect condensed water generated by the condenser.
21. The dehumidification device according to claim 19, characterized in that: The utility model further comprises a fan, wherein the fan is used for making the air heated by the heater form convection to desorb the porous moisture-absorbing material on the porous moisture-absorbing member.
22. The dehumidification device according to claim 21, characterized in that: The porous hygroscopic materials are arranged in a vertical direction, and the heated air passes through each of the porous hygroscopic materials.
23. The dehumidification device according to claim 19, characterized in that: It also includes a control unit, which controls the heater to start when the amount of adsorbed water of the porous hygroscopic material reaches or exceeds a first threshold, and controls the heater to shut down when the amount of adsorbed water reaches or is lower than a second threshold; the first threshold is higher than the second threshold.
24. The dehumidification device according to claim 23, characterized in that: The control unit comprises a gravimeter and a controller. The gravimeter is used to detect the weight of the porous hygroscopic member. The controller represents the amount of water adsorbed by the porous hygroscopic material according to the weight of the porous hygroscopic member.
25. The dehumidification device according to claim 23, characterized in that: The control unit includes a hygrometer and a controller. The hygrometer is used to detect the ambient humidity. The controller characterizes the amount of water adsorbed by the porous hygroscopic material according to the period after the heater is turned off and the period after the heater is turned on based on the ambient humidity detected by the hygrometer.
26. A method for preparing a porous hygroscopic material, characterized in that: It is used to prepare the porous hygroscopic material as claimed in any one of claims 1 to 16, characterized in that it comprises the following steps: Step 1: placing the hydrogel in an aqueous solution of a hygroscopic salt; Step 2: After the hydrogel swells, mechanical crushing is performed to form a micron-sized hydrogel-hygroscopic salt coating; and Step 3: Apply the hydrogel-hygroscopic salt coating to a hydrophilic and monolayer porous adsorption network and dry it.
27. The method for preparing a porous hygroscopic material according to claim 26, wherein: In step 1, the mass ratio of the hydrogel to the aqueous solution of the hygroscopic salt is between 1:40 and 1:20; in the aqueous solution of the hygroscopic salt, the molar ratio of the hygroscopic salt is between 0.5 mol / L and 3 mol / L.
28. The method for preparing a porous hygroscopic material according to claim 28, wherein: In step 1, the mass ratio of the hydrogel to the aqueous solution of the hygroscopic salt is preferably between 1:25 and 1:35; in the aqueous solution of the hygroscopic salt, the molar ratio of the hygroscopic salt is preferably between 1 mol / L and 2 mol / L.
29. The method for preparing a porous hygroscopic material according to claim 26, wherein: In step 2, the mechanical crushing is performed by stirring.
30. The method for preparing a porous hygroscopic material according to claim 26, wherein: In step 3, the method of coating the hydrogel-hygroscopic salt coating onto the porous adsorption network includes dip coating, spray coating, brush coating, rod coating, and spin coating.
31. The method for preparing a porous hygroscopic material according to claim 30, wherein: In step 3, the method of coating the hydrogel-hygroscopic salt coating onto the porous adsorption network is preferably dip coating.
32. A method for preparing a hydrogel, wherein the hydrogel is used to prepare the porous hygroscopic material as claimed in claim 16, characterized in that: The hydrogel is prepared by a free radical polymerization reaction of a first monomer containing a quaternary ammonium salt cationic group and a second monomer containing a carboxyl group and / or a carboxylate anionic group, a crosslinking agent and an initiator in the presence of a first solvent, followed by purification and drying; the free radical polymerization reaction is a front-end polymerization reaction; the crosslinking agent and the initiator are both hydrophilic; the first monomer and the second monomer are monomers containing a carbon-carbon double bond; and the first solvent is water or a hydrophilic alcohol.
33. The method for preparing the hydrogel according to claim 32, characterized in that: The cross-linking agent is preferably an acrylamide cross-linking agent; the initiator is preferably a peroxide or azo initiator; the first monomer is preferably acryloyloxyethyl trimethyl ammonium chloride and / or (3-acrylamide propyl) trimethyl ammonium chloride; the second monomer is preferably acrylic acid and / or sodium acrylate.
34. The method for preparing the hydrogel according to claim 32, wherein: The molar ratio of the second monomer to the first monomer is less than or equal to 5 to 3.
35. The method for preparing the hydrogel according to claim 34, characterized in that: The molar ratio of the second monomer to the first monomer is preferably 1:
3.
36. The method for preparing the hydrogel according to claim 32, characterized in that The free radical polymerization reaction also includes a third monomer, which is a monomer without an ionic group and containing a carbon-carbon double bond; the third monomer is preferably a monomer of acrylate, methacrylate, acrylamide or methacrylamide.
Citation Information
Patent Citations
Preparation method of PNIPAAm hydrogel-based raised fabric with super-strong moisture absorption and water release
CN116180446A
Moisture absorption type transparent hydrogel as well as preparation method and application thereof
CN119019610A
Battery based on hygroscopic hydrogel and preparation method thereof
CN112103560A
Recyclable dual-network heat dissipation hydrogel and preparation method thereof
CN117924742A
Natural porous sphagnum-based photo-thermal water collection material and application thereof
CN118480274A